Filmography of Philippine films, 1959-1989 - Junio, Arnulfo O. (1995)
This retrospective filmography deals with the popular Philippine feature films produced and/or exhibited in local movie houses from 1959 to 1989. Factual information on Filipino films was based entirely on secondary printed sources in the absence of the film itself. All pertinent articles in available issues of local and foreign newspapers, magazines, journals, annuals, and other materials published within the period 1959-1989 and possessed by various institutions, groups, and individuals were consulted.